Creating women's networks : a how-to guide for women and companies (Jossey-Bass New YorkUS, 1999)
Provides step-by-step guidance for creating a women's network, or for improving one that already exists. Advises on preliminary aspects of the process such as: identifying members' needs; deciding on purpose and activities; and getting organized. Looks at features of the on-going life of the network including: building support; implementing activities and programs that support the goals and mission; staying focused; and, dealing with problems. Includes relevant examples of successful networks; checklists for network leaders; and at each stage, a discussion of pitfalls.
Located in the Learning Resource Centre